2024
DOI: 10.1177/02654075241249172
|View full text |Cite
|
Sign up to set email alerts
|

Do different sources of sexuality education contribute differently to sexual health and well-being outcomes? Examining sexuality education in Spain and Portugal

David L. Rodrigues,
A. Catarina Carvalho,
Richard O. de Visser
et al.

Abstract: Sexuality education (SE) can be acquired through different sources. In a cross-sectional online study with Spanish and Portuguese participants ( N = 595), we examined differences between formal traditional sources (i.e., mandatory SE received in schools), formal modern sources (e.g., SE received in courses), informal traditional sources (e.g., talks with friends and family), and informal modern sources (e.g., pornography and online content) and their contribution to sexual health and well-being outcomes. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…However, these programs (much like the sexuality education curricula usually offered at schools in both countries; Picken, 2020) tend to have hygienist and biological approaches, mostly centering around the potential risks of sexual behavior (e.g., STI acquisition, unplanned pregnancy) and less often on its benefits (e.g., knowledge of one's body, sexual pleasure). Indeed, a recent study has shown that people who considered that sexuality education received during school years influenced their current thoughts and behaviors in sex are also more likely to protect their health (e.g., more focused on prevention; more likely to enact sexual communication; more likely to use condoms), but have less positive feelings about sex (Rodrigues et al, 2024). Our findings converge with the need to have a more comprehensive approach to sexual health and wellbeing (Ford et al, 2019), particularly considering that including pleasure in sexual and reproductive health programs can help improve condom use frequency (Zaneva et al, 2022).…”
Section: Extensions and Implicationsmentioning
confidence: 99%
“…However, these programs (much like the sexuality education curricula usually offered at schools in both countries; Picken, 2020) tend to have hygienist and biological approaches, mostly centering around the potential risks of sexual behavior (e.g., STI acquisition, unplanned pregnancy) and less often on its benefits (e.g., knowledge of one's body, sexual pleasure). Indeed, a recent study has shown that people who considered that sexuality education received during school years influenced their current thoughts and behaviors in sex are also more likely to protect their health (e.g., more focused on prevention; more likely to enact sexual communication; more likely to use condoms), but have less positive feelings about sex (Rodrigues et al, 2024). Our findings converge with the need to have a more comprehensive approach to sexual health and wellbeing (Ford et al, 2019), particularly considering that including pleasure in sexual and reproductive health programs can help improve condom use frequency (Zaneva et al, 2022).…”
Section: Extensions and Implicationsmentioning
confidence: 99%